Opening Injection Pressure Is Higher in Intraneural Compared With Perineural Injections During Simulated Nerve Blocks of the Lower Limb in Fresh Human Cadavers. Issue 3 (1st May 2017) - Vermeylen, Kris; Hermans, Marlies; Soetens, Filiep; Vereecke, Evie; Steinfeldt, Thorsten; Groen, Gerbrand; Hadzic, Admir; Van de Velde, Marc
Abstract : Background and Objectives: Needle-induced nerve trauma and intraneural injection can lead to neurologic injury during peripheral nerve blocks. In this study, we assessed the utility of opening injection pressure (OIP), time to OIP, and rate of rise to OIP in detecting needle-nerve contact and intraneural injection. Methods: Five common ultrasound-guided blocks of the femoral, saphenous, subgluteal sciatic, tibial, and common peroneal nerves were simulated in 10 fresh cadavers. Opening injection pressure was defined as peak psi in the 60-second interval during which the injection is initiated. Pressure-time curves were constructed separately for intraneural and perineural injections for each of the 5 nerves studied. Results: Opening injection pressure was higher for intraneural than for perineural injections ( P < 0.001), ranging from 21.5 psi (1111.9 mm Hg) to 25.8 psi (1334.2 mm Hg) for intraneural injections and from 3.8 psi (196.5 mm Hg) to 6.1 psi (315.5 mm Hg) for perineural injections. Time to OIP tended to be shorter for intraneural than for perineural injections, particularly for the subgluteal sciatic, tibial, and common peroneal nerves. Curves of intraneural injections had steep slopes with high peaks; curves of perineural injections had low slopes followed by plateaus. Rise to OIP was greater for intraneural than for perineural injections. Conclusions: In our fresh human cadaver model, OIP detected intraneural needle placement. Monitoring of OIP could be useful in detecting and/or preventing intraneural injection during nerve blocks in the clinical setting.